Metodologi Al-Albānī Dalam Menetapkan Keṡaḥīhan Hadis Atas Kitab Silsilah Al-Ṡaḥīḥah - Muhammad Rafiâ€™iy Rahim,; Maggading, Muhammad Ismail (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2022)
The authenticity of the hadith is not the same as the authenticity of the Qur'an, where the Qur'an has received direct legitimacy from Allah SWT. In contrast to the hadith, it takes a lot of in-depth research to see how the quality of the hadith is both in terms of its sanad and meaning. There have been many hadith experts who have tried to mix various methods in order to maintain the existence of the hadith itself. Among the many experts, al-Albānī is one of them who devoted most of his life to exploring the system that applies in the study of hadith. As a lover of hadith, al-Albani does not necessarily accept the hadith he reads even though they have been studied previously. This caution is what makes al albāni create his own method, although it cannot be denied that al albān's method is not much different from the methods of his predecessors